1997
DOI: 10.1002/(sici)1097-4555(199710)28:10<803::aid-jrs151>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos fibre identification by Raman microspectroscopy

Abstract: Raman microspectroscopy has been shown to be a very powerful technique for the identiÐcation and characterization of small mineral Ðbres, with little or no sample preparation. Such spectra are sensitive to the composition of the mineral and can often be used to distinguish between similar species. The technique can be employed for the identiÐcation of single micrometre-sized Ðbres. Vibrational spectra were obtained from Ðve asbestos reference standards for comparison with four non-Ðbrous analogues. The di †ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 2 publications
9
37
0
Order By: Relevance
“…4) agrees well with literature data of chrysotile (e.g., Bard et al 1997;Kloprogge et al 1999;Rinaudo et al 2003;Auzende et al 2004). However, Kloprogge et al (1999) list additional Raman bands at 374, 607, 629, and 709 cm -1 originating from band deconvolution in the low-frequency range.…”
Section: Raman and Ftir Spectra At Ambient Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…4) agrees well with literature data of chrysotile (e.g., Bard et al 1997;Kloprogge et al 1999;Rinaudo et al 2003;Auzende et al 2004). However, Kloprogge et al (1999) list additional Raman bands at 374, 607, 629, and 709 cm -1 originating from band deconvolution in the low-frequency range.…”
Section: Raman and Ftir Spectra At Ambient Conditionssupporting
confidence: 91%
“…In general, older literature document just two IR active bands at 3651 and 3697 cm -1 (Farmer 1974) and two Raman active bands at around 3685 and 3700 cm -1 (Bard et al 1997), respectively. These findings are mostly caused by the lack of band deconvolution.…”
Section: Raman and Ftir Spectra At Ambient Conditionsmentioning
confidence: 99%
“…To realize sorting, it is necessary to understand the physical and chemical properties of waste (e.g., density or electromagnetic property) and to determine whether the waste contains asbestos. The purpose of studies on the identification of asbestos [13][14][15][16] is to develop an accurate method for asbestos analysis. Bassani et al [17] reported the use of remote sensing to detect asbestos in roofing sheets, which enabled scanning…”
Section: Introductionmentioning
confidence: 99%
“…To realize sorting, it is necessary to understand the physical and chemical properties, such as density and magnetic property, or to determine whether the waste contains asbestos fiber or not. The purpose of studies on the identification of asbestos [10][11][12][13] is to develop an accurate method for asbestos analysis. The use of remote sensing to detect asbestos in roofing sheets, which enabled scanning of ACM by batch in large urban areas was reported [14].…”
Section: Introductionmentioning
confidence: 99%